2023
DOI: 10.24239/pdg.vol12.iss1.391
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Social and Religious Character of Students at Qurratu A'yun High School Through Extracurricular Activities

Abstract: Religious education in schools is expected to have a significant impact on the development of students' religious and social character so as to prevent them from immoral social behavior. This research tries to identify extracurricular activities that help improve the social and religious character of students. This research uses qualitative methodologies, with in-depth interviews providing as data collecting technique. The data were subsequently analysed utilising triangulation techniques by modifying existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Fitriani found other obstacles, such as the environment, lack of parental awareness, students having difficulty memorizing, playing with gadgets, and additional assignments from school. In line with this, Fakhrurrozi found that extracurricular activities can also develop students' religious and social character 12 .…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Fitriani found other obstacles, such as the environment, lack of parental awareness, students having difficulty memorizing, playing with gadgets, and additional assignments from school. In line with this, Fakhrurrozi found that extracurricular activities can also develop students' religious and social character 12 .…”
Section: Introductionmentioning
confidence: 61%
“…Based on the previous explanation, the results of this research validate multiple prior studies, including Fakhrurrozi's research, which asserted that habituation of behavior is an efficient method for molding students' character. The consistent patterns of behavior exhibited in extracurricular activities can have a significant impact on students' attitudes towards relationships within the school environment and in the classroom 25 . Additional studies corroborate the findings of this research, including Hambali and Yulianti assert that implementing religious character education through extracurricular activities in schools yields a substantial and favorable influence on students' growth, particularly in their capacity to comprehend and implement Islamic religious principles in their social interactions 26 .…”
Section: Improving Islamic Religious Education Learning Outcomes At S...mentioning
confidence: 99%